43.9k views
5 votes
Solve by substitution:y=x-35y=-4x

User Guerline
by
5.6k points

1 Answer

4 votes

Answer:

(7, -28)

Step-by-step explanation:

Given the system of equations:


\begin{gathered} y=x-35 \\ y=-4x \end{gathered}

Substitute the second equation into the first:


\begin{gathered} y=x-35 \\ -4x=x-35 \\ -4x-x=-35 \\ -5x=-35 \\ \text{Divide both sides by -5} \\ (-5x)/(-5)=(-35)/(-5) \\ x=7 \end{gathered}

Next, solve for y:


\begin{gathered} y=-4x \\ =-4(7) \\ y=-28 \end{gathered}

The solution to the system of equations is:


(7,-28)

User Nick Campion
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.